Mutations affecting assembly and stability of tubulin: evidence for a nonessential beta-tubulin in CHO cells. - Boggs, B (1987)
Eight strains of Chinese hamster ovary (CHO) cells having an assembly-defective beta-tubulin were found among revertants of strain Cmd 4, a mutant with a conditional lethal mutation in a beta-tubulin gene (F. Cabral, M. E. Sobel, and M. M. Gottesman, Cell 20:29-36, 1980). The altered beta-tubulins in these strains have electrophoretically silent alterations or, in some cases, an increase or a decrease in apparent molecular weight based on their migration in two-dimensional gels. The identity of these variant proteins as beta-tubulin was confirmed by peptide mapping, which also revealed the loss of distinct methionine-containing peptides in the assembly-defective beta-tubulins of lower apparent molecular weight. The altered mobility of these beta-tubulin polypeptides was not the result of a posttranslational modification, since the altered species could be labeled in very short incubations with [35S]methionine and were found among in vitro-translated polypeptides by using purified mRNA. In at least one strain, an altered DNA restriction fragment could be demonstrated, suggesting that an alteration occurred in one of the structural genes for beta-tubulin. Assembly-defective beta-tubulin was unstable and turned over with a half-life of only 1 to 2 h in exponentially growing cells. This rapid degradation of a tubulin gene product resulted in approximately 30% lower steady-state levels of both alpha- and beta-tubulin yet did not affect the growth rate of the cells or the distribution of the microtubules as judged by immunofluorescence microscopy. These results argue that CHO cells possess a beta-tubulin gene product that is not essential for survival.